2008
DOI: 10.1373/clinchem.2007.095992
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Biomarkers for Blood-Based Colorectal Cancer Screening

Abstract: BACKGROUND:Sensitive, specific blood-based tests are difficult to develop unless steps are taken to maximize performance characteristics at every stage of marker discovery and development. We describe a sieving strategy for identifying high-performing marker assays that detect colorectal cancer (CRC)-specific methylated DNA in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
332
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 441 publications
(350 citation statements)
references
References 16 publications
(22 reference statements)
10
332
1
7
Order By: Relevance
“…As described in a previous report and our preliminary study (13,14), p75NGFR was considered to be one of the highly methylated genes in colorectal cancer. To validate these results, a 418-bp fragment located at 44928023-44928440 of NM_002507 (NCBI accession number) and spanning intron 1 of the p75NGFR gene was identified, and primers for MSP and BGS were designed in the region of exon 1 to detect the methylation status of the p75NGFR gene (Fig.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…As described in a previous report and our preliminary study (13,14), p75NGFR was considered to be one of the highly methylated genes in colorectal cancer. To validate these results, a 418-bp fragment located at 44928023-44928440 of NM_002507 (NCBI accession number) and spanning intron 1 of the p75NGFR gene was identified, and primers for MSP and BGS were designed in the region of exon 1 to detect the methylation status of the p75NGFR gene (Fig.…”
Section: Resultssupporting
confidence: 55%
“…For example, it has been shown to exert a tumor-promoting effect in brain tumors and melanomas (11,12), whereas it has also been proposed as a potential tumor suppressor in bladder (7), stomach (9) and liver cancers (10). However, with the exception of a previous study reporting hypermethylation of p75NGFR in the serum of patients with colorectal cancer (13), no other studies to date have reported the methylation status, expression level, or function of p75NGFR in colorectal cancer. Therefore, we conducted this study to determine the role of p75NGFR in the initiation, progression and prognosis of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery process to identify methylation markers for colorectal cancer included both, using arbitrarily primed PCR methods as well as methylation hybridization arrays, and methylation specific PCR [21]. It is clear from this and other studies that the challenge in the approach is not finding methylation differences, of which there are hundreds, but in filtering these differences to identify target sequences that have practical value for the intended diagnostic purpose [22].…”
Section: Sept9 Promoter Methylation-discovery and Development Of Methmentioning
confidence: 99%
“…This objective imposed the marker criteria: 1) Sequences should be differentially methylated in cancer tissue and preferably in adenoma/polyp tissue; 2) Amenable to PCR amplification following bisulfite conversion; 3) Absent in cell free DNA in healthy subjects; 4) Present in detectable quantities in cell free DNA extracted from plasma or serum of patients with colorectal cancer. A collection of several hundred DNA methylation differences discovered in genome wide and microarray studies were selected based on the ability to develop PCR assays, then counter selected based on positivity using peripheral blood leukocyte DNA, and subsequently DNA pools isolated from plasma of healthy subjects, leading to a shortlist of 3 candidate markers [22]. Of these, the promoter methylation status of the SEPT9 gene showed the best correlation with colorectal cancer both in tissue DNA and in cell free DNA isolated from plasma [22,23].…”
Section: Sept9 Promoter Methylation-discovery and Development Of Methmentioning
confidence: 99%
“…Validation data of MCTA-Seq shows that it is highly reproducible and sensitive, with the detection limit down to as low as 7.5 pg (~2.5 haploid genome equivalents). Existing biomarkers that are frequently hypermethylated in human cancers [8], such as VIM, SEPT9, NDRG2 and RASSF1 [8], could be detected with high sensitivity by using MCTA-Seq. The method, although limited by the requirement of the CGCGCGG sequence content, is genome-wide and offers sufficient information about CpG island methylation changes in HCC.…”
mentioning
confidence: 99%